Treatment outcomes of rapid desensitisation protocols for chemotherapeutic agents and monoclonal antibodies following hypersensitivity reactions. Issue 5 (May 2014) - Kuo, J. C.; Hawkins, C.; Yip, D.
Abstract Background Hypersensitivity reactions (HSR) to chemotherapeutic agents and monoclonal antibodies are common and may limit further therapeutic options. Drug desensitisation aims to induce a temporary clinical unresponsiveness to drug antigens so the causative drugs of HSR can continue to be administered. Rapid desensitisation using standardised protocols has been conducted by the Department of Immunology at The Canberra Hospital for patients who developed HSR to chemotherapeutic agents and monoclonal antibodies. Aims This retrospective audit reviewed the safety and efficacy of the desensitisation protocols used for patients across the Capital Region Cancer Service (CRCS). Methods Patients across the CRCS who received rapid desensitisation were identified through a search of archived correspondence. Clinical files and pharmacy records were analysed to determine protocol safety and efficacy. Results From June 2006 to July 2013, 13 patients underwent rapid desensitisations to oxaliplatin, carboplatin, docetaxel or rituximab. A total of 25 desensitisations was conducted with 21 (84%) achieving full target dose without inducing recurrent HSR. As a result, nine patients were successfully desensitised and continued to receive treatment without any further HSR. Desensitisation was aborted in three patients because of recurrence of HSR, which was not of a greater severity than the initial HSR. After successful desensitisation, seven patients were able to resume the regular protocols without requiring additional supervision. Conclusion Rapid desensitisation to various chemotherapeutic agents and monoclonal antibodies with standardised protocols used across CRCS is safe and effective; it provides a feasible treatment option enabling continuation of effective regimens in the setting of HSR.